(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Teaching English for Specific Purposes (ESP) is a specialized area of English language instruction, which focuses on teaching English to non-native speakers with specific career or professional goals, such as business professionals. One innovative approach to teaching ESP, particularly business terms, is the Total Physical Response (TPR) method. This article delves into the use of TPR for teaching business terminologies to ESP learners, exploring its benefits, strategies, and implementation.